GROWTH, IMMUNITY, AND RESISTANCE OF CATFISH (Clarias sp.) REARED IN BIOFLOC SYSTEM SUPPLEMENTED WITH Bacillus NP5 AGAINST Aeromonas hydrophila INFECTION - Suleman, Gabriella Augustine; Widanarni, Widanarni; Yuhana, Munti; Afiff, Usamah (Agency for Marine and Fisheries Extension and Human Resources, 2024)
Catfish Clarias sp. is one of the leading commodities in demand and has economic value. Low survival due to cannibalism and disease is a serious problem. To overcome these problems is application of bioflocs and probiotics Bacillus NP5. This study aimed to analyze the appropriate dose of Bacillus NP5 probiotic addition to the biofloc system to improve the health status, growth performance, water quality, and resistance to A. hydrophila. The catfish fry (Clarias sp.) with an average weight of 1.79±0.05 g was used in the experiment for 40 days, reared in tanks with the dimension of 60×30×35 cm3. The experiment applied a completely randomized design (CRD) of five treatments with three replicates, namely KN (negative control), KP (positive control), BFT (biofloc application without probiotic bacteria), BFT4 (biofloc application with Bacillus NP5 104 CFU mL-1), BFT6 (biofloc application with Bacillus NP5 106 CFU mL-1). Treatments tested were challenged with A. hydrophila density 104 CFU mL-1 by immersion, except the negative control. After 40 days of rearing, biofloc and Bacillus NP5 treatments had a significant effect (P < 0.05) on growth performance, immune response, water quality, total bacteria in water and the gut compared to the control treatment (P < 0.05). In addition, total A. hydrophila in liver, kidney and water were lower (P < 0.05) in BFT4 and BFT6 treatments than the control. The conclusion of this study is that the bioflocs supplemented with Bacillus NP5 improved the growth performance, immune response and resistance of catfish to A. hydrophila infection.